MicroRNAs and long non-coding RNAs in pancreatic cancer: From epigenetics to potential clinical applications - Bravo-Vázquez, Luis Alberto; Frías-Reid, Natalia; Ramos-Delgado, Ana Gabriela; Osorio-Pérez, Sofía Madeline; Zlotnik-Chávez, Hania Ruth; Pathak, Surajit; Banerjee, Antara; Bandyopadhyay, Anindya; Duttaroy, Asim K.; Paul, Sujay (Elsevier, 2023)
MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are two relevant classes of non-coding RNAs (ncRNAs) that play a pivotal role in a number of molecular processes through different epigenetic regulatory mechanisms of gene expression. As a matter of fact, the altered expression of these types of RNAs leads to the development and progression of a varied range of multifactorial human diseases. Several recent reports elucidated that miRNA and lncRNAs have been implicated in pancreatic cancer (PC). For instance, dysregulation of such ncRNAs has been found to be associated with chemoresistance, apoptosis, autophagy, cell differentiation, tumor suppression, tumor growth, cancer cell proliferation, migration, and invasion in PC. Moreover, several aberrantly expressed miRNAs and lncRNAs have the potential to be used as biomarkers for accurate PC diagnosis. Additionally, miRNAs and lncRNAs are considered as promising clinical targets for PC. Therefore, in this review, we discuss recent experimental evidence regarding the clinical implications of miRNAs and lncRNAs in the pathophysiology of PC, their future potential, as well as the challenges that have arisen in this field of study in order to drive forward the design of ncRNA-based diagnostics and therapeutics for PC.